The Value of Working Compared to Gambling : Are College Students Risk Takers? - Smits, Rochelle R. (My University, 2009)
Pathological gambling, labeled a disorder by the American Psychological Association, is responsible for maladaptive consequences in over eighteen percent of the U.S. adult population. Given the limited understanding of the etiology of the disorder, there currently is a need for an experimental model of gambling. The goal of the present study is to validate a new gambling paradigm and achieve a more thorough understanding of the relationship between environmental factors (e.g., between income and the odds of success at gambling) that may contribute to the development and maintenance of gambling behavior.
Color poster with text, image, and graph (Spring 2009)
Keywords: Risk-taking (Psychology); Gambling--Psychological aspects; Compulsive gambling--Psychological aspects; College students--Psychology; Work--Psychological aspects; Posters